Effect of silver nanoparticles prepared by Streptomyces. spp on some pathogenic bacteria - Hussain A. Abod; kalil I. Bander; Salah S. Zain-Al-Abddeen (Tikrit Journal of Pure Science)
Tow species of Streptomyces isolated from the industrial district area in the Kirkuk city and two species represented Streptomyces hygroscopicus and Streptomyces parvulus. were used to detected their ability to prepare silver nanoparticles. The results showed change in color silver nitrate solution 1mM to dark brown, Studied the spectrum of absorption of UV, visible spectroscopy of the solution silver particles nano second step in making sure the formation of particles and found to be located on the wavelength of 400 nm to bacteria Streptomyces parvulus also show that the X-ray diffraction peaks were at (311-200-111) and at the angle (31.73 and 48.70 and 58.30). .Additinary the results showed clear images in the scanning electron microscope size and shape .the bacteria Streptomyces hygroscopicus was a wavelength of 280 nm .etbin that silver nano particles solution with inhibitory effect on the two types of multi-antibiotic resistance antibiotics bacteria E.coli and P. mirabilis, which amounted to (27,27,29) mm against the bacteria Escherichia coli at a concentration of 100% were (30,30,29) mm when the concentration 100% against Proteus mirabilis